2017
DOI: 10.1021/acsmedchemlett.6b00416
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mechanistic Evaluation of Hemozoin-Inhibiting Triarylimidazoles Active against Plasmodium falciparum

Abstract: In a previous study, target based screening was carried out for inhibitors of β-hematin (synthetic hemozoin) formation, and a series of triarylimidazoles were identified as active against Plasmodium falciparum. Here, we report the subsequent synthesis and testing of derivatives with varying substituents on the three phenyl rings for this series. The results indicated that a 2-hydroxy-1,3-dimethoxy substitution pattern on ring A is required for submicromolar parasite activity. In addition, cell-fractionation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…The Pathogen Box features a related spirotetrahydro‐β‐carboline MMV031011 ( 453 ), whose bromo analogue ( 454 ) has been reported as a lead antimalarial from the TCAMS . Egan and co‐workers had also reported a series of triarylimidazoles (e.g., 455 ) as hemozoin inhibitors . Although structurally distinct from 455 , clotrimazole ( 456 ) is an imidazole‐containing antifungal, which inhibits the heme‐containing CYP51 responsible for sterol biosynthesis.…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…The Pathogen Box features a related spirotetrahydro‐β‐carboline MMV031011 ( 453 ), whose bromo analogue ( 454 ) has been reported as a lead antimalarial from the TCAMS . Egan and co‐workers had also reported a series of triarylimidazoles (e.g., 455 ) as hemozoin inhibitors . Although structurally distinct from 455 , clotrimazole ( 456 ) is an imidazole‐containing antifungal, which inhibits the heme‐containing CYP51 responsible for sterol biosynthesis.…”
Section: Malariamentioning
confidence: 99%
“…This, along with Pathogen Box compound MMV030734 ( 558 ), are yet to feature in follow‐up studies. However, similar compounds ( 559 and 560 ), which coincidentally share some structural homology with Egan's hemozoin inhibitors, have been reported as inhibitors of human B‐Raf kinase, which is a member of the RAF serine/threonine kinases and forms part of the MAP kinase (MAPK) cascade, responsible for progression of the cell cycle and ultimately apoptosis . The plasmodial orthologue of RAF kinase inhibitory protein (RKIP), referred to as PfPE‐PB1, has been shown to regulate the activity of P. falciparum calcium‐dependent protein kinase 1 ( Pf CDPK1) .…”
Section: Malariamentioning
confidence: 99%
“…The majority of compounds inhibited β‐hematin in a narrow range, which was superior to that of chloroquine. Three compounds including 53 , displaying encouraging, albeit moderate anti‐plasmodial activity, with no chloroquine cross‐resistance . Through an expanded library of triarylimidazoles, Jeena and co‐workers identified several additional compounds with promising β‐hematin inhibitory activity.…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…According to the structures and skeletons of these hit compounds and other compounds obtained from the HTS screening, a number of research were reported in recent years about the related modification of these compounds as lead compounds. Egan et al reported the subsequent synthesis and testing of derivatives with varying substituents on the three phenyl rings for the scaffold triaryl imidazoles (eg, 128 , Figure A), and revealed that the digestive vacuole, including pH trapping, play a crucial role in the relative potency of a compound's ability to inhibit cellular Hz formation . On the other hand, they selected the benzamide derivatives, that originated from the scaffold N ‐phenylbenzamide, have been purchased and synthesized to explore SARs of parasite activity, cytotoxicity, and the inhibitory effect of HZ formation in P. falciparum , as shown in Figure B.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…224,225 During the screening of St Jude Children's Research Hospital, thirteen hits displayed efficacy against the β-Hz formation as shown in Figure 28 cellular Hz formation. 226 On the other hand, they selected the benzamide derivatives, that originated from the scaffold N-phenylbenzamide, have been purchased and synthesized to explore SARs of parasite activity, cytotoxicity, and the inhibitory effect of HZ formation in P. falciparum, 221,227 as shown in Figure 29B. Besides, a novel series of quinoline triazole amide analogues has been designed, synthesized, and evaluated the activities against P. falciparum CQS D10 strain, and derivative 129 (44) was found to be the most inhibitory activity for HZ formation.…”
Section: The Discovery Of Quinoline Art and Xanthone-derived Antimentioning
confidence: 99%